COLLECTIVE MEMORIES OF WEST-SUMATRAN EARTHQUAKE AND THEIR RELATION TO COMMUNITY RESILIENCE - Dona Eka Putri (Universitas Gunadarma, 2011)
Indonesia’s geographical conditions are in the high earthquake-prone that requires a seriouseffort in disaster mitigation, so that the losses inflicted disasters both physically andpsychologically can be minimized. This study aims to find out the positive aspects ofexperiencing traumatic event in community that experienced natural disasters, in which withthese memories help the community become more resilient. In this study, interview conductedafter Padang earthquake (West Sumatra) on September 2009. The participants were 7 adults,whom experiencing the event directly. Interview conducted in Indonesian or Minanglanguage. The approach was narrative, asked participants to tell their story of the disasterand how the disaster has changed their community. Analysis was performed with a qualitativeapproach. From the interviews conducted, the finding obtained is the theme of narrative givenby participants can be grouped into two categories; the strategy of evacuation and things thatminimize the impact.